Constraints facing tourism entrepreneurs in South Africa: A study in the Gauteng and Mpumalanga Provinces, South Africa - Nieman, Gideon (University of Pretoria, 2013)
Thesis (DCom (Business Management))--University of Pretoria, 2002.